Quand Thot devient babouin: Essai de datation et d’interprétation de l’apparition de la forme simiesque du dieu - Larcher, Cédric (Zeitschrift für ägyptische Sprache und Altertumskunde, 2016)
The baboon is a recognized hypostasis of Thoth, however it is not until the reign of Amenhotep III that the animal is explicitly referring to the god in the iconography. This connection can be explain by the predilection at this time for the animal forms of the gods. It is related too to the theological orientations that emerge around the nature of the kingship and its link with the god Ra and the Moon. It seems that this new characterstical form of Thot is highlighted at the occasion of the king’s sed-festival.